2021
DOI: 10.21037/tcr-20-3540
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes in gastric cancer by integrated bioinformatics analysis

Abstract: Background: Gastric cancer (GC) is one of the most common cancer worldwide. With the high rates of metastasis and recurrence, its overall survival remains poor at the present time. Hence, seeking new potential therapeutic targets of GC is important and urgent.Methods: We retrieved the gene expression profiles and clinical data from The Cancer Genome Atlas (TCGA) datasets. After screening differentially expressed genes (DEGs), we carried out the survival analysis for overall survival to pick out robust DEGs. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Also, the GO enrichment analysis was shown that DEGs in the N and NAT lists were enriched in some similar terms, such as extracellular matrix organisation, retinol metabolism, and metabolism of xenobiotics by cytochrome P450. These GO terms were also have been reported for DEGs of GC in the previous reports [20][21][22]. However, some KEGG and GO terms were different for the N and NAT lists.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, the GO enrichment analysis was shown that DEGs in the N and NAT lists were enriched in some similar terms, such as extracellular matrix organisation, retinol metabolism, and metabolism of xenobiotics by cytochrome P450. These GO terms were also have been reported for DEGs of GC in the previous reports [20][21][22]. However, some KEGG and GO terms were different for the N and NAT lists.…”
Section: Discussionsupporting
confidence: 83%
“…Also, the top protein module of the PPI network of the N and NAT list were enriched in the same KEGG terms. These KEGG terms were also reported for GC by Lu et al [20], who analysed seven microarray datasets with NAT tissues as calibrators, Sun et al [21], who analysed the TCGA database, Li et al [22], who analysed two microarray datasets, Zhang et al [23], who analysed three microarray datasets, and Zhang et al [24], who analysed one microarray dataset and TCGA database. Also, the GO enrichment analysis was shown that DEGs in the N and NAT lists were enriched in some similar terms, such as extracellular matrix organisation, retinol metabolism, and metabolism of xenobiotics by cytochrome P450.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Deviations in this pathway significantly contribute to tumor invasion and metastasis (Krabbe et al, 2016). Furthermore, there is an association between the occurrence of stomach cancer and systemic lupus erythematosus (SLE) (Sun et al, 2021). In support of this connection, Clarke et al (2021) conducted a meta-analysis and found that individuals with SLE had a significantly higher likelihood of developing gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“…They found that IRX4 was downregulated in the mouse stomach after irradiation with 6 or 12 Gy X-rays, and they also observed that radiation resulted in atrophy of the gastric mucosa and abnormal morphology of chief and parietal cells. Using the TCGA database, Sun and colleagues [ 110 ] identified that IRX4 expression was downregulated in GC patients and associated with their survival outcomes.…”
Section: Iroquois Family Genes In Gastric Cancermentioning
confidence: 99%